Maternal Methadone Dose, Placental Methadone Concentrations, and Neonatal Outcomes - de Castro, Ana (Clin Chem, 2011)
BACKGROUND: Few investigations have used placenta as an alternative matrix to detect in utero drug exposure, despite its availability at the time of birth and the large amount of sample. Methadone-maintained opioid-dependent pregnant women provide a unique opportunity to examine the placental disposition of methadone and metabolite [2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP)], to explore their correlations with maternal methadone dose and neonatal outcomes, and to test the ability to detect in utero exposure to illicit drugs. METHODS: We calculated the correlations of placental methadone and EDDP concentrations and their correlations with maternal methadone doses and neonatal outcomes. Cocaine- and opiate-positive placenta results were compared with the results for meconium samples and for urine samples collected throughout gestation. RESULTS: Positive correlations were found between placental methadone and EDDP concentrations (r = 0.685), and between methadone concentration and methadone dose at delivery (r = 0.542), mean daily dose (r = 0.554), mean third-trimester dose (r = 0.591), and cumulative daily dose (r = 0.639). The EDDP/methadone concentration ratio was negatively correlated with cumulative daily dose (r = 0.541) and positively correlated with peak neonatal abstinence syndrome (NAS) score (r = 0.513). Placental EDDP concentration was negatively correlated with newborn head circumference (r = 0.579). Cocaine and opiate use was detected in far fewer placenta samples than in thrice-weekly urine and meconium samples, a result suggesting a short detection window for placenta. CONCLUSIONS: Quantitative methadone and EDDP measurement may predict NAS severity. The placenta reflects in utero drug exposure for a shorter time than meconium but may be useful when meconium is unavailable or if documentation of recent exposure is needed.